2017
DOI: 10.3390/w9100791
|View full text |Cite
|
Sign up to set email alerts
|

Batch Test Screening of Industrial Product/Byproduct Filter Materials for Agricultural Drainage Water Treatment

Abstract: Filter treatment may be a viable means for removing the nitrate (NO 3 − ), phosphate (PO 4 3− ), and pesticides discharged with agricultural drainage waters that cause adverse environmental impacts within the U.S. on local, regional, and national scales. Laboratory batch test screening for agricultural drainage water treatment potential was conducted on 58 industrial product/byproduct filter materials grouped into six categories: (1) high carbon content media; (2) high iron content media; (3) high aluminum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Thus, material selection for an application should be site-specific. It cannot be simply stated that SW is better or worse than GI like it is currently done in the Fe 0 remediation literature [83][84][85]. For example, Allred [84] recently evaluated the suitability of 58 industrial aggregates (products and by-products), including 8 Fe 0 specimens as filter materials for the treatment of agricultural drainage water.…”
Section: Batch Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, material selection for an application should be site-specific. It cannot be simply stated that SW is better or worse than GI like it is currently done in the Fe 0 remediation literature [83][84][85]. For example, Allred [84] recently evaluated the suitability of 58 industrial aggregates (products and by-products), including 8 Fe 0 specimens as filter materials for the treatment of agricultural drainage water.…”
Section: Batch Experimentsmentioning
confidence: 99%
“…By doing so, the specificity of Fe 0 , making it applicable for decades, is not addressed [46][47][48][49][50]. The approach used by Allred [84] is commonplace in the recent literature and was introduced already in the 1990s [6,88,89], resulting in disqualifying Fe 0 for water treatment [89] or recommending it [6,88]. Since then, a legitimate scepticism on the efficiency of Fe 0 for water treatment is available within the remediation community [90,91].…”
Section: Batch Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile it has been intensively demonstrated that pure sand filters (biosand filters) just partly address biological contamination [72][73][74][75][76]. Amending biosand filters with Fe 0 is progressively established as an affordable and applicable alternative to more sophisticated systems [77,78]. The more important feature is that in-situ-generated ferrous and ferric oxides are contaminant collectors [17,19,36] besides impairing the permeability [20,24].…”
Section: The Service Life Of Fe 0 Filtersmentioning
confidence: 99%